Engineering Topological Spin Hall Effect in 2D Multiferroic Material - Kaiying Dou; Zhonglin He; Jiangyu Zhao; Wenhui Du; Ying Dai; Baibiao Huang; Yandong Ma (Advanced Science, 2024)
Abstract Topological spin Hall effect (TSHE), promoted by coupling between noncoplanar spins and real‐space topology, is a significant phenomenon in condensed matter physics. However, the control of TSHE characteristics is missing due to its intrinsic robustness, and such fundamental difficulty prevents it from being used for spintronics up to now. Here, a rational design approach is demonstrated to engineer TSHE in a controllable and reversible fashion. Through symmetry and model analysis, it is unveiled that antiferromagnetic topological charge, as well as Lorentz forces, acted on conduction electrons, can be coupled with Dzyaloshinskii‐Moriya interaction chirality for antiferromagnetic bimerons in 2D multiferroic materials. Such coupling guarantees the ferroelectric control of TSHE. Using first‐principles calculations and atomic spin model simulations, the validity of this mechanism is further demonstrated in multiferroic monolayer CuCr2Se4 with experimental feasibility. The alter‐chirality of the Dzyaloshinskii‐Moriya interaction is found to play a crucial role in realizing this mechanism. This results extend TSHE to be used in spintronics and open a new direction for spintronics research.